2008
DOI: 10.1007/s11274-008-9718-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of melanin pigment from Pleurotus cystidiosus (telomorph of Antromycopsis macrocarpa)

Abstract: Melanins are enigmatic pigments that are produced by a wide variety of microorganisms including several species of bacteria and fungi. For more than 40 years, fungi have been known to produce pigments called melanins. Melanin pigment production by mushrooms was not intensively studied. The present study was carried out on isolation and characterization of melanin from an edible mushroom Pleurotus cystidiosus var. formosensis. The mushroom produced dark mucous mass of hyaline arthrospores on mycelium. The corem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
74
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 49 publications
15
74
0
11
Order By: Relevance
“…Enochs et al (1993) described a standardised and effective test for the identification of melanin pigment by identifying the presence of stable population of organic free radical signal. The G -value of fungal melanin is reported to be 2.0012 (Selvakumar et al 2008). Termitomyces albuminosus melanin G -value is found to be somewhat higher which could be due to O-semiquinone free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enochs et al (1993) described a standardised and effective test for the identification of melanin pigment by identifying the presence of stable population of organic free radical signal. The G -value of fungal melanin is reported to be 2.0012 (Selvakumar et al 2008). Termitomyces albuminosus melanin G -value is found to be somewhat higher which could be due to O-semiquinone free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…UV-VIS spectrum was obtained in the range 190–750 nm using UV–VIS spectrophotometer (Shimadzu UV-2400) 0.1 mol/L NaOH as reference (Suryanarayanan et al 2004; Selvakumar et al 2008). A standard melanin spectrum was also obtained using Sepia officinalis melanin (Sigma, Aldrich Chemicals, India).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanin originates from different nature sources, such as Osmanthus fragrans seeds (Wang et al 2006), Pleurotus cystidiosusand (Selvakumar et al 2008), and silky fowl (Tu et al 2009), and has been reported to have excellent free radicals scavenge activity. Squid ink melanin is the most typical melanin usually used as melanin standard with strong free radical protection activities (Menon and Haberman 1977).…”
Section: Introductionmentioning
confidence: 99%
“…It participates readily in processes of electron transfer and is an efficient free-radical scavenger [71][72][73]. Beverages such as tea, coffee and cocoa and foodstuffs such as grapes, bananas and edible fungi contain melanin-like pigments [74,75]. There have been reports that melanin could be among the causes for the phenomenon of increased survival of fungi growing on nuclear test sites after receiving multiple lethal radiation doses (after soil irradiation with 6400 Gy) [76].…”
Section: Radioprotective Properties Of Melaninmentioning
confidence: 99%